Counseling on Prevention of Stunting Events in Babies in the New Village of Ladang Bambu, Medan Tuntungan District in 2020 - Helena Fransysca; Suriati Lubis (Institute of Computer Science (IOCS), 2020)
The purpose of this study was to find out whether mothers understand the prevention of stunting in infants. Increase mother's knowledge when her baby experiences growth and development failure in her baby and increase mother's knowledge about the signs and symptoms of stunting in infants. The types and forms of activities of this activity are providing material to mothers regarding stunting in infants, giving snacks to infants.